Aligned vertical growth of zinc oxide nanorods on glass substrates using optimum hydrothermal synthesis technique - Mohd Hafiz Jali; Md Ashadi Md Johari; Hazli Rafis Abdul Rahim; Haziezol Helmi Mohd Yusof; Aminah Ahmad; Mohamad Faizal Baharom; Sulaiman Wadi Harun (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper reported an optimized hydrothermal synthesis technique to grow zinc oxide (ZnO) nanorods vertically on the normal microscope glass. ZnO nanorods exhibited various advantages such as strong binding energy, non toxicity, large surface to volume ratio and versatility for optical detections. However, the growth of nanorods which aligned vertically on the glass substrates is rather complicated. It required a thorough process based on optimized concentration, growth duration, growth temperature and solvent variations. The morphological structure result has shown an exceptional vertical growth of the nanorods on the glass surfaces which increase the nanorods density. The optimized synthesis technique produced high density ZnO nanorods up to 3 ???? 1013 nanorods/m2 which is double as compared to conventional synthesis technique.